The Nexus between Corporate Governance and Economic, Social and Environment (ESE) Practices: Bangladeshi Banking Paradox - Hossen, Amzad; Swarna, Farjana Akter; Toha, Md Abu (Business Management and Strategy, 2024)
This study aimed to investigate the relationship between corporate governance and sustainability practices at 45 scheduled commercial banks in Bangladesh. The study specifically focused on the impact of corporate governance on bank sustainability practices, using the Global Reporting Initiative (GRI-4) sustainability guidelines. The resource-based view theory was used to explain the relationship between corporate governance and sustainability practices. Panel data used for this analysis was derived from the annual and sustainability disclosure reports of these banks from 2017 to 2021. This study explores dimensions of corporate governance, including board size, independent board members, CEO duality, gender diversity, audit committees, risk management committees, and audit firm size, highlighting their importance in strategic decision-making. It also explores sustainability practices from a corporate perspective, focusing on economic, social, and environmental performance indicators and emphasizing the importance of strategic resource allocation and disclosure. Four hypotheses were formed, and ordinary least squares (OLS) regression was employed to test the relationship between corporate governance and bank sustainability practices. The statistical results showed that CG has a direct effect on firms overall sustainability as well as social and environmental sustainability practices. It was also seen that the size of the board has a significant effect on the overall sustainability measures (ESE). The study suggests that pro-active measures should be taken to improve sustainability practices in Bangladesh.